2017
DOI: 10.1124/dmd.117.077883
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Impact of P-glycoprotein and Breast Cancer Resistance Protein on the Brain Distribution of Catechol-O-Methyltransferase Inhibitors

Abstract: P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) are clinically important efflux transporters that act cooperatively at the blood-brain barrier, limiting the entry of several drugs into the central nervous system (CNS) and affecting their pharmacokinetics, therapeutic efficacy, and safety. In the present study, the interactions of catechol--methyltransferase (COMT) inhibitors (BIA 9-1059, BIA 9-1079, entacapone, nebicapone, opicapone, and tolcapone) with P-gp and BCRP were investigated to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…This does not invalidate the concept of the CMFDA assay but complicates the mechanistic explanation of toxicity for a certain compound if non bile acid efflux transporters are involved. For example, entacapone may be a more potent inhibitor of BCRP [35] than BSEP. On the other hand, the present CMFDA assay is performed in human hepatocytes with drug metabolizing capacity that would not be provided by the vesicle assay.…”
Section: Discussionmentioning
confidence: 99%
“…This does not invalidate the concept of the CMFDA assay but complicates the mechanistic explanation of toxicity for a certain compound if non bile acid efflux transporters are involved. For example, entacapone may be a more potent inhibitor of BCRP [35] than BSEP. On the other hand, the present CMFDA assay is performed in human hepatocytes with drug metabolizing capacity that would not be provided by the vesicle assay.…”
Section: Discussionmentioning
confidence: 99%
“…Then we employed MDCK II and MDCK-MDR1 cell models to estimate the role of P-gp involvement into cinobufotalin transport. The efflux ratio (ER) value was higher than 2.0 in MDCK-MDR1 cell monolayers, indicated that P-gp mediate the active transport of cinobufotalin (Bicker et al, 2017). Furthermore, cinobufotalin was, for the first time, identified as the substrate of P-gp with the net flux ratio was higher than 2.0 (Bicker et al, 2017; Liu L. et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The efflux ratio (ER) value was higher than 2.0 in MDCK-MDR1 cell monolayers, indicated that P-gp mediate the active transport of cinobufotalin (Bicker et al, 2017). Furthermore, cinobufotalin was, for the first time, identified as the substrate of P-gp with the net flux ratio was higher than 2.0 (Bicker et al, 2017; Liu L. et al, 2018). After preincubation with verapamil, the noticeably reduction of net flux ratio ascertain cinobufotalin was the substrate of P-gp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when biomedical outcomes change over time, machine learning methods integrating the outcomes need to account for these dynamics. For example, cancer cells, bacteria, and viruses evolve rapidly to gain drug resistance [24], and ignoring the dynamics of drug response can lead to poor performance in predicting drug efficacy and toxicity.…”
Section: Challenges In Data Integration For Biology and Medicinementioning
confidence: 99%